The male chauvinist pig : a history - Willett, Julie A. (Chapel Hill : The University of North Carolina Press, 2021)
"In the social upheavals of the 1960s and 1970s, a series of stock characters emerged to define and bolster white masculinity. Alongside such caricatures as "the Playboy" and "the Redneck" came a new creation: "the Male Chauvinist Pig." Coined by second-wave feminists as an insult, the Male Chauvinist Pig was largely defined by an anti-feminism that manifested in boorish sexist jokes. But the epithet backfired: being a sexist pig quickly transformed into a badge of honor worn proudly by misogynists, and, in time, it would come to define a strain of right-wing politics. Historian Julie Willett tracks the ways in which the sexist pig was sanitized by racism, popularized by consumer culture, weaponized to demean feminists, and politicized to mobilize libertine sexists to adopt reactionary politics"--
Includes bibliographical references (pages 159-168) and index.
Keywords: Sexism in political culture -- United States; Anti-feminism -- United States; Conservatism -- United States -- History -- 20th century; Conservatism -- United States -- History -- 21st century; American wit and humor -- Political aspects -- History